(untitled) (Praxis Educativa, 2025)
This paper analyzes the relation between the expansion of the Argentine university system in recent decades and effective inclusion, understood not only as access but also as student retention and graduation. Within a free and open-access system—where over 80% of the more than two million enrolled students attend public universities—this research investigates the extent to which institutions have developed internal conditions that support complete educational trajectories, in alignment with national policies. Two indicators were constructed for this purpose: “Institutional Conditions for Inclusion,” based on an analysis of external institutional evaluation reports from CONEAU; and “Institutional Inclusion Level,” derived from official statistics on retention and graduation provided by the SSPU. The results reveal significant heterogeneity among universities and show that variables such as founding year, size, or geographic location do not independently explain levels of inclusion. Instead, the analysis suggests that student trajectories are more strongly associated with institutional conditions aimed at supporting them. The findings contribute to conceptual debates on inclusion and democratization in higher education and highlight the value of CONEAU’s institutional diagnostics as tools for understanding and strengthening inclusion conditions. Furthermore, the proposed model offers analytical tools to support institutional decision-making and monitor the impact of university policies on students’ actual academic progress.